2012
DOI: 10.1021/jp210106b
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Crystal Structure and Electronic Structure on Photocatalytic H2 Evolution and CO2 Reduction over Two Phases of Perovskite-Structured NaNbO3

Abstract: Cubic and orthorhombic NaNbO 3 were fabricated to study the effects of crystal structure and electronic structure on the photocatalytic activities in detail. The samples were characterized by X-ray diffraction, field emission transmission electron microscopy, high-resolution transmission electron microscopy, UV−visible absorption spectroscopy, and X-ray photoelectron spectroscopy. The photocatalytic activities of the two phases of NaNbO 3 have been assessed by H 2 evolution from aqueous methanol solution and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(178 citation statements)
references
References 46 publications
(66 reference statements)
4
170
1
1
Order By: Relevance
“…e vertical black dashed lines correspond to the experimental ground state volumes. [34] Given are the lattice parameter a, equilibrium unit-cell volume V 0 , the bulk modulus B 0 and its pressure derivative B ′ 0 , and the direct E Table 2. e electronic band structure calculated using the PBEsol functional and based on the PBEsol ground state volume is shown in Figure 5(c).…”
Section: Monoclinic Pm Phasementioning
confidence: 99%
“…e vertical black dashed lines correspond to the experimental ground state volumes. [34] Given are the lattice parameter a, equilibrium unit-cell volume V 0 , the bulk modulus B 0 and its pressure derivative B ′ 0 , and the direct E Table 2. e electronic band structure calculated using the PBEsol functional and based on the PBEsol ground state volume is shown in Figure 5(c).…”
Section: Monoclinic Pm Phasementioning
confidence: 99%
“…This yield is relatively low compared with the conversion of water splitting. [14][15][16][45][46][47][48][49][50][51][52][53][54] The conversion efficiency and [ 45] ). [14] ).…”
Section: Discussionmentioning
confidence: 99%
“…3. [51] Li et al discussed the photocatalytic activities of CO 2 reduction over the cubic and orthorhombic NaNbO 3 in a gas phase system and found that the CO 2 reduction activity over the cubic NaNbO 3 was nearly twice that of the orthorhombic NaNbO 3 . These results might be due to the unique electron structure of cubic NaNbO 3 , which may support electron excitation and transfer.…”
Section: Niobatesmentioning
confidence: 99%
See 2 more Smart Citations